Chitosan for Direct Bioflocculation Processes - Lichtfouse, Eric; Morin-Crini, Nadia; Fourmentin, Marc; Zemmouri, Hassiba; Nascimento, Inara Oliveira Carmo do; Queiroz, Luciano Matos; Mohd Yuhyi, Mohd Tadza; Picos-Corrales, Lorenzo A.; Pei, Haiyan; Wilson, Lee D.; Crini, Grégorio (Springer, 2019)
Coagulation-flocculation is a major process allowing to remove suspended particles from municipal and industrial wastewater. This process commonly involves metal salts as coagulants and synthetic organic polymers as flocculants. Although those chemicals are cheap, efficient, available and easy to use, they have drawbacks such water pollution by metals, and production of large amounts of toxic sludges. Therefore, safer biocoagulants and bioflocculants of biological origin are currently developed. For instance, the direct flocculation process involves water-soluble, ionic organic polymers, and thus do not need the addition of metal coagulants. In particular, chitosan and byproducts have been recently designed as bioflocculants to remove particulate matter and dissolved pollutants. Chitosan is a partially deacetylated polysaccharide obtained from chitin, a biopolymer extracted from shellfish sources. Chitosan exhibits various physicochemical and functional properties of interest for many environmental applications.